Innovations in Indian financial system: remedy for economic growth?. Issue 11 (2nd November 2018) - Pandey, Alok; Banwet, D. K.
ABSTRACT: This paper gives an overview of key innovations for financial system reforms undertaken by successive governments in India since the 1990s. These are namely liberalisation, demonetisation, digitisation and implementation of GST. Out of these digitisation, demonetisation and implementation of GST demonetisation have been claimed as disruptive innovations by the experts. We examine the impact of innovations such as financial liberalisation, digitisation and demonetisation on some key macro-economic parameters of economic growth in India through available literature and secondary data. The analysis is done over a period of 1970–2014 to test whether innovations such as digitisation and demonetisation had a statistically significant impact on the economy.